Macocha idealna: aktywność Anny Luizy z Mycielskich Radziwiłłowej w świetle francuskiej korespondencji dyplomatycznej (1764–1765) - Bajer, Jakub; Mariani, Andrea (Studia Europaea Gnesnensia, 2014)
The paper offers an insight into the diplomatic activities of princess Anna Luiza Radziwiłłowa nee Mycielska, second wife and widow of the great general of Lithuania, Michał Kazimierz “Rybeńko” Radziwiłł, in the aftermath of the election of Stanisław August to the Polish throne. The main sources comprise diplomatic correspondence between France and Gdańsk, where the princess lived during the exile of her stepson, following his opposition to the new king. The paper aims at showing how Anna Luiza tried to gain political support from France as well as how her efforts were perceived by the French diplomacy.